Comparison of the UEScope videolaryngoscope with the Macintosh laryngoscope during simulated cardiopulmonary resuscitation: A randomized, cross-over, multi-center manikin study - Szarpak, Lukasz (Medicine (Baltimore), 2018)
BACKGROUND: Endotracheal intubation (ETI) can be challenging, especially in life-threatening situations such as cardiopulmonary resuscitation (CPR). Videolaryngoscopes aim to ease ETI, but effort is still widely discussed. This study intended to investigate 2 different airway devices regarding the success rate of ETI during ongoing chest compressions. METHODS: This randomized, cross-over, multi-center manikin trial included 85 experienced paramedics actively working in the emergency medicine service. After a standardized training session, all paramedics underwent 3 airway scenarios using both, direct laryngoscopy using a Macintosh blade and videolaryngoscope (the UEScope): normal airway without chest compressions, normal airway with uninterrupted chest compressions, and difficult airway with uninterrupted chest compressions. The primary outcome was successful ETI, defined as successful placement of the endotracheal tube within the manikin's trachea. Secondary outcomes were number of intubation attempts, time to successful ETI, time to best glottis view, best percent of glottic opening, best glottic view score (Cormack and Lehane), occurrence of dental trauma, ease of use, and willing to reuse in real-life situations. RESULTS: The UEScope provided a better glottis visualization, and higher first pass intubation success rate compared to direct laryngoscopy in all 3 scenarios. The overall intubation success was higher, and the intubation time was shorter with the UEScope in scenario B and scenario C, but was comparable in scenario A. Dental compression occurred less often using the UEScope and paramedics rated intubation using the UEScope easier compared to direct laryngoscopy in all 3 airway scenarios. CONCLUSION: In simulated CPR scenarios, intubation with the UEScope resulted in a better glottis visualization, a higher intubation success, and a shorter intubation time compared to Macintosh laryngoscope (MAC). Moreover, in situations where the airway is difficult for ETI especially by the paramedic, the UEScope would be a better choice than the MAC. Further studies are needed to confirm these results in real-life patients.